Pengembangan Kawasan Wista Pantai Selatbaru Dengan Pendekatan Arsitektur Tepian Air - Amalia Nurussifa; Wahyu Hidayat; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Selatbaru Beach is one of the best beaches and a place of recreation for Bengkalis residents, this is evidenced by the number of tourists visiting Selatbaru Beach increasing every year. In Selatbaru Beach there are several problems that make the value of tourism on the beach lack of architectural touch, so from these problems came the idea to increase tourism value and economic value by developing the Selatbaru Coast tourism area. The method used is the Waterfront Architecture Approach which in principle accommodates various activities such as residential, business, commercial, and entertainment with the aim of developing the physical and non-physical potential of the waterfront, as well as providing solutions to problems and potential problems found in Selatbaru Beach. Local cultural elements need to be incorporated into the region to present a tourism area that has an identity, through the concept of "sampan jong" which is one of the game traditions of the Selatbaru people who are able to form regional images that are formulated macro and micro.Keywords : Selatbaru Beach, tourism, waterfront